Kinetics of FCC to HCP Transformation During Aging Heat Treatment of Co–28Cr–6Mo Alloy Fabricated by Laser-Powder Bed Fusion - Antunes, L. H. M.; Beres, Miloslav; Hoyos Quintero, John Jairo; Novotný, L.; de Abreu, H. F. G.; da Silva Farina, P. F. (Springer, 2023)
Fil: Antunes, L. H. M.. Universidade Estadual de Campinas; Brasil